Boarding School Caregivers' Parenting Patterns in Shaping Students' Religious Character: A Qualitative Study at SMP Insan Cendekia Madani - Siskandar Siskandar; Akhmad Shunhaji; Tetra Nurtianty (STAI Hubbulwathan Duri, 2025)
The development of students' religious character is a central objective in Islamic boarding school education. SMP Insan Cendekia Madani in South Tangerang adopts the Madani Curriculum, which integrates national, Cambridge, and Islamic curricula, to foster students’ piety (taqwa) and etiquette (adab). This study aims to examine the parenting patterns employed by dormitory supervisors in shaping students’ religious character. A qualitative descriptive method was used, with data collected through observations, in-depth interviews, and document analysis. Thematic analysis was applied to identify key patterns in supervision and mentorship. Findings reveal that dormitory supervisors serve as educators, mentors, companions, and surrogate parents, following the Islamic framework of al-Waalid, al-Ustadz, and as-Shohib. A tiered mentoring system with a 1:16 supervisor-student ratio supports intensive character guidance. Programs such as congregational prayer, Qur’an recitation, dzikir, and digital-based religious mentoring effectively instill Islamic values. However, challenges include inconsistent emotional bonding, varied supervisory approaches, and difficulties in accommodating diverse student needs. These findings underscore the importance of adaptive, student-centered parenting strategies. It is recommended that schools enhance supervisors’ emotional intelligence, provide certified Islamic parenting training, and integrate psychological support systems to improve the overall effectiveness of character education in Islamic boarding schools.